Pendekatan Tematik Qur'an dan Hadits sebagai Landasan Pembinaan Akhlak Sehari-Hari di MA Al Husna Dawuhan Krejengan Probolinggo - Sholehatul Muarrifah; Ainur Rofiq Sofa (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This study explores the methods of moral education based on the thematic approach from the Qur'an and Hadith, as well as its application in guiding human morality in daily life. The primary focus of the research is to uncover the moral values embedded in the Qur'an and Hadith and to understand the methods employed to instill these values. This study employs a qualitative approach with a literature review to systematically and practically describe the moral values. The findings reveal that the Qur'an and Hadith not only provide normative guidelines for morality but also offer various educational methods, such as exemplification, habituation, advice, storytelling, and experiential learning. This moral education is highly relevant in shaping an Islamic-character generation that is not only intellectually competent but also possesses high moral integrity. A strong moral education can serve as a solution to address various moral and social challenges in the modern era.